Contrast-Enhanced 3D MR Angiography of the Carotid Artery: Comparison with Conventional Digital Subtraction Angiography - Remonda, Luca; Senn, Pascal; Barth, Alain; Arnold, Marcel; Lövblad, Karl-Olof; Schroth, Gerhard (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Since 1996, several preliminary studies have shown the usefulness of contrast material–enhanced MR angiography for imaging supraaortic vessels. The aim of this study was to compare the accuracy of contrast-enhanced 3D MR angiography with that of digital subtraction angiography (DSA) in the evaluation of carotid artery stenosis.METHODS: A blinded comparison of first-pass contrast-enhanced MR angiography with conventional DSA was performed in 120 patients (240 arteries). MR angiography was performed with a 1.5-T magnet with gradient overdrive equipment, by using a coronal radiofrequency-spoiled 3D fast low-angle–shot sequence after the intravenous injection of gadodiamide. The guidelines of the North American Symptomatic Carotid Endarterectomy Trial for measuring stenosis of the internal carotid artery were applied on maximum intensity projection (MIP) images and conventional catheter angiograms.RESULTS: Grading of stenoses on MR angiograms agreed with grading of stenoses on DSA images in 89% of arteries. In the severe stenosis group (70–99%), agreement was 93%. All internal carotid occlusions (n = 28) and seven of nine pseudo-occlusions were accurately detected with contrast-enhanced MR angiography. The correlation between MR angiography and DSA for determination of minimal, moderate, and severe stenoses and occlusion was statistically significant (r = 0.91, P< .001).CONCLUSIONS: This investigation with a large number of patients confirms that contrast-enhanced MR angiography could become a diagnostic alternative to DSA in the treatment of patients with carotid artery disease.